31 Eight years of cardiac screening in high risk irish population. (5th October 2017) - Sulaiman, H; Connaughton, H; Reynolds, A; Brennan, C; Ward, D
Abstract : Introduction: Sudden cardiac death (SCD) is defined as death from cardiac arrhythmia within one hour of symptom onset. Aetiology may be structural cardiac conditions including ischaemic heart disease (IHD) which is multifactorial in origin, and cardiomyopathies including hypertrophic cardiomyopathy (HCM), dilated cardiomyopathy (DCM), and arrhythmogenic cardiomyopathy (AC, previously known as ARVC), all of which may be genetic in origin and inherited. Sudden arrhythmic death syndrome (SADS) is SCD with structurally normal heart at post mortem. Primary arrhythmic syndromes causing SADS include long QT syndrome (LQTS), Brugada syndrome (BrS) and catecholaminergic polymorphic ventricular tachycardia (CPVT), again often hereditary. In addition to coping with a devastating loss, families are faced with a fear that surviving family members could be affected. Could preventable action amongst the surviving at risk of SCD be undertaken? Can people with no risk be reassured? These are the purpose of this cardiac screening facility. The Centre for Cardiac Risk in Younger Persons (CRYP), a largely charitably funded service was opened in Tallaght Hospital in 2007, with a full-time dedicated facility open since November 2008. Assessment of surviving relatives and affected individuals is led by a consultant cardiologist with specific training in inherited cardiac conditions. The assessment includes taking a complete history with compilation of detailed family pedigree, examination, non-invasive cardiac investigations and, where appropriate genetic analysis collaborating with the Centre for Medical Genetics, Our Lady's Children Hospital. Post mortem reports of deceased relatives are always obtained. Baseline cardiac investigations include electrocardiogram (ECG), echocardiogram (ECHO), exercise stress test either bicycle (WHO protocol) or treadmill (Bruce Protocol) and Holter monitor for up to 7 days. Drug provocation (Ajmaline and Epinephrine) tests are done to unmask BrS and LQTS or CPVT as appropriate. Further diagnostic tools may be employed including loop recorders (external and internal), coronary angiography (invasive or CT), cardiac magnetic resonance imaging and electrophysiological testing. Methods: This is a retrospective review of all patients seen in the CRYP from November 2008 to end 2015. Percentages were calculated based on number of individuals or families reviewed as appropriate. Results: 4778 individuals representing 3486 families were assessed (many attending on multiple occasions over the time period for follow-up). 54% were males. Individuals were classified according to reason for referral (e.g. diagnosis in the family) and or conditions identified. These results are presented in Table 1. Table 2 summarises further breakdown of the SADS family screening. In total 17% of 1056 individuals were diagnosed with a cardiac condition, and 83% of 1056 individuals could be reassured and discharged. 1934(40 %) of all normal individuals continue to attend for further investigations. Conclusions: A significant number of individuals and families have benefited from the largely charitably funded dedicated service over the 7 year period presented. Contrary to published prevalence from other populations including the USA, LQTS is the most common diagnosis in our population followed by HCM. A large number of patients with cardiac conditions have been identified hopefully protected from the worst possible consequences of their conditions. Of equal importance a large number of unaffected individuals have been reassured and can benefit from the improved quality of life such peace of mind brings. The remainder of patients who are currently unaffected, in the absence of clinically useful genetic results, will require long-term follow-up in circumstances where conditions such as cardiomyopathies which display age-related penetrance are a risk. Expansion and public funding of facilities such as ours should, in our opinion, be considered a priority for the Irish population.